Factors Influencing the Physical Fitness Status among Middle School Students in Jiangxi Province, China - Zou, Zeyu (International Journal of Social Sciences and Public Administration, 2024)
This study aims to determine the physical health status of middle school students and its influencing factors as a basis for enhancing physical education courses, aiming to improve students’ physical fitness. With the proliferation of technological devices, teenagers are spending more time in indoor activities, affecting their physical development. Through the implementation of national sunshine sports and related policies, students’ physical fitness has improved, but there is still the problem of focusing on academics and neglecting sports. Research results show that students generally have good cardiopulmonary function, but have higher obesity rates. Personal, environmental, school and social factors have a significant impact on students’ physical health status. To solve this problem, comprehensive measures need to be taken to improve physical education courses, encourage students to actively participate in sports activities, and improve overall health.